Building climate-resilient health systems in Sierra Leone: addressing the dual burden of infectious and climate-related diseases - Umaru Sesay; Augustus Osborne (Infectious Diseases of Poverty)
Abstract Climate change presents a profound challenge to global health, disproportionately affecting low-income countries like Sierra Leone. This opinion examines the dual burden of infectious and climate-related diseases and their implications for Sierra Leone’s health systems. Rising temperatures and changing rainfall patterns intensify vector-borne diseases such as malaria and Lassa fever, while flooding exacerbates waterborne diseases in overcrowded urban areas. Concurrently, climate-driven food insecurity worsens malnutrition, particularly among children, and heat stress contributes to the growing prevalence of non-communicable diseases. These overlapping health crises strain Sierra Leone’s fragile health system, characterized by inadequate infrastructure, workforce shortages, weak surveillance systems, and limited financial resources. The dual disease burden not only increases morbidity and mortality but also deepens existing health inequities and inequalities. To address these challenges, this opinion underscores the need for climate-resilient health policies and systems. Key recommendations include strengthening healthcare infrastructure, building workforce capacity through targeted training, fostering community-based adaptation strategies, and enhancing international collaboration and financing. Establishing robust research and data systems is also critical to monitor and mitigate climate-related health impacts. By prioritizing response to dual burden of infectious and climate-related diseases within health policy frameworks, Sierra Leone can build a resilient health system that safeguards public health and promotes sustainable development.